Perspective of Islamic Business Ethics on Work Relations between Farmers and Shallot Traders in Baraka District, Enrekang Regency - AkbarAkbar Hidayat Ahmad; Andi Bahri S.; Muhammad Kamal Zubair; Muliati; Damirah (Universitas Muhammadiyah Palu, 2024)
This research aims to conduct an assessment of the perspective of Islamic business ethics on working relationships between farmers and shallot traders in the district. Baraka. The research uses qualitative descriptive methods. The research results were obtained using primary data sources in the form of interview data with shallot farmers and onion traders in Baraka District, Enrekang Regency, while secondary data was obtained based on references from published journals and scientific articles. Data analysis techniques use data collection techniques, data reduction, preparation and drawing conclusions. The research results found that the perspective of Islamic business ethics is in line with the practice of cooperation between farmers and shallot traders in Kec. Baraka. This is proven by Islamic business ethics which surround the motives of shallot traders to establish cooperative relationships with farmers. The economic constraints faced by shallot farmers in cultivating their land will of course have alternative solutions if they are able to utilize existing cooperative relationships with traders.